VD_FINDINFO Arrêt / 2021 / 63 vom 19. Januar 2021 - VD Tribunal cantonal (2021)
AM, LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, TRAITEMENT À L'ÉTRANGER | 24 LAMal, 32 LAMal, 34 al. 2 LAMal, 36 al. 1 OAMal, 36 al. 2 OAMal